Analisis Perbedaan Materi Pokok Pembelajaran Sejarah Peradaban Islam Pada Kurikulum 2013 dan Kurikulum Prototipe 2022 - Basuki (AL MURABBI, 2022)
The burden of learning achievement in the history of Islamic civilization in the subjects of Islamic Religious Education and Character Education (PAI and BP) in the 2013 curriculum is quite heavy. Because learning achievement must reach four dimensions of achievement indicators (spiritual attitudes, social attitudes, knowledge, skills), this condition became one of the backgrounds for implementing the 2022 prototype curriculum. This study aims to identify and analyze the burden of learning achievement of the history of Islamic civilization in PAI and BP subjects in the 2013 and 2022 prototype curricula. The research library with the primary data sources being "2013 curriculum policy" and "2022 prototype curriculum policy". This study uses content analysis which finds that learning material on the history of Islamic civilization in PAI and BP subjects in the 2022 prototype curriculum is not forced to achieve four achievement indicators but is adjusted to the type of material in each phase. In addition, it was also found that the learning material for the history of Islamic civilization in PAI and BP subjects in the 2022 prototype curriculum was more comprehensive than the 2013 curriculum. Thus, the 2022 prototype curriculum could recover the problems of the 2013 curriculum